2018
DOI: 10.5625/lar.2018.34.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Higher incidence of sperm granuloma in the epididymis of C57BL/6N mice

Abstract: C57BL/6N mice are inbred strains widely used in biomedical research. Hence, a large amount of basic data has been accumulated. However, in the field of histopathology, spontaneous data for relatively younger mice that are used more frequently are not yet abundant, in contrast to data for older mice and their neoplastic lesions. To acquire the essential background data required by various research and toxicological assessments, 120 mice of the C57BL/6N strain (10 and 13 weeks of age) were collected from two ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Spermatic granulomas are common in young and middle-aged men. Park et al [10] found that the incidence of spermatic granuloma at a young age is higher than that at an old age in mouse experiments, indicating that the incidence of spermatic granuloma is related to age. The patient in this study was a middle-aged male.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatic granulomas are common in young and middle-aged men. Park et al [10] found that the incidence of spermatic granuloma at a young age is higher than that at an old age in mouse experiments, indicating that the incidence of spermatic granuloma is related to age. The patient in this study was a middle-aged male.…”
Section: Discussionmentioning
confidence: 99%
“…. Повреждение структурных компонентов гемато-эпидидимального барьера приводит к развитию инфертильных состояний и формированию спермальных гранулем [1, 15,19,32]. Повреждения эпителия эпидидимиса могут быть вызваны повышением давления семенной жидкости (обтурационные повреждения), а также в результате действия внешних факторов, таких, как бактериальная инфекция, воспаление, химические агенты и лекарственные препараты [1,12,15,19,27,30,37].…”
unclassified